1996
DOI: 10.1002/j.1939-4640.1996.tb01785.x
|View full text |Cite
|
Sign up to set email alerts
|

Media and Dilution Procedures Tested to Minimize Handling Effects on Human, Rabbit, and Bull Sperm for Computer‐Assisted Sperm Analysis (CASA)

PAUL B. FARRELL,
ROBERT H. FOOTE,
MARGARET M. McARDLE
et al.

Abstract: Proper handling of semen prior to computer‐assisted sperm analysis (CASA) is critical if the analysis is to be representative of the fresh sample. The effects of diluting medium or dilution and holding time before CASA on multiple sperm characteristics were studied. Four replicates of unselected semen samples from each of eight human donors were diluted with phosphate‐buffered saline (PBS)‐glucose plus bovine serum albumin (BSA), with Tyrode's albumen lactate pyruvate (TALP), and with high‐potassium TALP (K‐TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…CASA can significantly improve the accuracy and precision of dog semen analysis methods. Furthermore, CASA has been successfully used in other mammalian species, such as bulls, boars, and humans, to improve IVF outcomes ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CASA can significantly improve the accuracy and precision of dog semen analysis methods. Furthermore, CASA has been successfully used in other mammalian species, such as bulls, boars, and humans, to improve IVF outcomes ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports describing mammalian sperm preparation using swim-up and Percoll gradient methods have been published ( 28 , 29 ). However, these reports are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have shown that pure chitosan microcapsules did not aggregate with sperm either, did not affect cell viability and motility parameters, and presumably did not interfere with the AI system used in vivo. As the commercial diluent used is designed for use at RT instead of 37•C, it is possible that the pronounced decrease in sperm motility over time can be attributed to the temperature and the time incubation applied during the experiment [44,45].…”
Section: Discussionmentioning
confidence: 99%